Relevance of astrocytes/microglia communication for NLRP3 signalling in the CNS - proof of concept in an ex vivo epilepsy model - Almeida, Catarina Isabel Carvalhas (2018)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia